Screening of Ipomoea tuba leaf extract for identification of bioactive compounds and evaluation of its in vitro antiproliferative activity against MCF-7 and HeLa cells - Venkateswarulu, Thirupati Chinna (Array, 2020)
Mangroves contain a wide range of bioactive compounds with pharmacological activities. In the present study, we analysed the separation and detection of phytoconstituents with the methanol extract of Ipomoea tuba leaf using gas chromatography-mass spectrometry (GC-MS) and tested its in vitro cytotoxicity effect against MCF-7 and HeLa cells. Phytochemical compounds such as docosanoic, octadecatrienoic and cis-9-octadecanoic acids, triterpenoid γ-sitosterol, and terpene alcohol in methanol extract of I. tuba leaf were identified. Furthermore, in vitro antiproliferative activity of the extract of I. tuba leaf was evaluated using MCF-7 and HeLa cells. The results indicated a reduction of cell viability of 37.43 and 41.89 % of MCF-7 and HeLa cells respectively. The methanol extract of I. tuba leaf proved to be effective in protecting the cells against oxidative stress. This is the first report on the in vitro cytotoxicity effect of I. tuba leaf extract on MCF-7 and HeLa cells.